Investigation of the Effect of Vitamin K Prophylaxis on Newborn Screenings Tests in Newborns: Effect of Vitamin K on Newborn Screenings Tests - Caglayan, Murat (Journal of Medical Biochemistry, 2023)
Background: Routine screening for hereditary disorders in newborns includes screening for treatable metabolic and endocrine disorders, such as biotidinase deficiency, galactosemia, maple syrup urine disease, hypothyroidism, and cystic fibrosis. Incorrect test results may be encountered due to the use of vitamin K. To investigate the interference effect of vitamin K on neonatal screening tests and to raise awareness of erroneous measurements.Methods: Heel blood samples were taken from 25 newborns born in a neonatal intensive care unit. Dry blood C0, C2, C3, C4, C4DC, C5:1, C5OH, C5DC, C6, C6DC, C8, C8:1, C8DC, C10, C10:1, C10DC, C12, C14, C14:1, C14:2, C16, C16:1, C18, C18:1, C18:2, C18:OH, methylglutaryl, valine, leucine/isoleucine, methionine, phenylalanine, argininosuccinic acid, aspartate, alanine, arginine, citrulline, glycine, ornithine, and glutamate tests were studied using the tandem mass spectrometry (MS) method. The results of the heel blood samples obtained before and after the application of vitamin K1 (Phyto menadione) were compared.Results: In two studies conducted with in vitro and in vivo tests, C0, C2, C3, C4, C4DC, C5, C5OH, C6, C8, C10, C10:1, C14, C16, C16:1, C18, C18:1, methylglutaryl, phenylalanine, argininosuccinic acid, tyrosine, aspartate, arginine, citrulline, glycine, and glutamine were all significantly elevated (p < 0.05).Conclusion: Heel blood samples may yield false results due to vitamin K administration. In the case of doubtful results, a new sample should be taken and the measurement should be repeated.
Keywords: Vitamin K; heel blood; hereditary disorders; tandem MS; interference; newborn